PENGARUH KOMPRES AIR HANGAT TERHADAP NYERI PADA PENDERITA FLEBITIS DI RS DKT JEMBER - Dwi Rahayu Setiyowati; Luh Titi Handayani; Fitriana Putri (Universitas Muhammadiyah Jember, 2017)
Pain is a complex sensation that can only be felt by those affected, a person's response to pain is different from one person to another. Phlebitis is an inflammation that occurs in veins that can cause redness, swelling and pain. One way to reduce pain is by applying warm compresses. The type of warm water compress that give the warm water compress it dry. In a dry warm water compresses can withstand temperatures longer than warm water compress wet, but it has little risk of making sunburn. The purpose of this study is to determine the effect of warm water compresses to pain in patients with phlebitis in RS DKT Jember. This study is a pre-experimental design, the design of one group pre-test post-test design. Samples in this study were 30 respondents using sampling techniques qouta. Collecting data using a scale VAS (Visual Analog Scale) and the questionnaire ID Pain. The results obtained showed that the measurement of pain in patients with phlebitis before being given a warm water compress Pain ID values obtained with the average value of 1.0333 and VAS pain scale (Visual Analog Scale) after being given a warm water compress on RS DKT Jember obtained average value 0.590 average. Statistical test results obtained by using the Wilcoxon test results obtained p value=0, 000, p0.05, meaning there is an influence does warm water compresses to pain in patients with phlebitis in RS DKT Jember. This study was recommended to nursing personnel to use warm compresses as an alternative for reducing pain than using pharmacological therapy.Keywords: Dry Warm Water Compresses, Pain, Phlebitis.